THE INFLUENCE OF LAYOUT AS A GROWTH FACTOR IN SALES AT RETAIL: a case study at the company Highlight Fashion and Accessories in João Pinheiro-MG - Silva, Kenia Araújo da (2020)
This article is about the importance of a good layout for retail stores, taking into account a specific case of "Boutique Enhancement and Fashion", located in the city of João Pinheiro. This study has special relevance for the academic environment, because it aims to deepen knowledge and put into practice the content studied in the course, in order to formulate strategies so that companies obtain more profits and stand out in the market in terms of competitiveness. In the course of the article we discussed the definition of layout, its types and their importance. The case study was based on 10 questions for the interviewees, obtaining satisfactory results that point in the direction that the target audience values the physical image of the stores, appreciate good service and appreciate when the products are well exposed because this facilitates at the time of purchase decision. Initially, bibliographic research was carried out in management and administration magazines, books, monographs, theses, dissertations and scientific articles. The last stage was composed by the analysis, separation and organization of data, reason why, it was possible to obtain a greater prominence in the study of layout adequacy.